THE INFLUENCE OF SALES PROMOTION, PRODUCT QUALITY AND CONSUMER DISSATISFACTION WITH BRAND TRANSFER DECISIONS (STUDY ON EX BLACKBERRY USERS IN BANDUNG REGENCY) - Dewi Yolanda (Jurnal Ekonomi, 2022)
This study aims to determine the influence of sales promotion, product quality and consumer dissatisfaction with blackberry smartphone brand transfer decisions in Bandung Regency. The method used is descriptive analysis, the types and sources of data obtained in this study are primary data and secondary data. The data collection technique in this study is to spread questionnaires, with a sample of 100 respondents who are respondents who move Blackberry brand smartphones to other brand smartphones. The study used four variables: Sales Promotion (X1), Product Quality (X2), Consumer Dissatisfaction (X3) and Brand Transfer Decisions(Y). The results of the study using multiple regression analysis showed that sales promotion had no significant effect on brand transfer decisions, product quality had a significant effect on brand transfer decisions and consumer dissatisfaction had a significant effect on brand transfer decisions. Together/ simultaneous sales promotion, product quality and consumer dissatisfaction have a significant effect on brand transfer decisions. Later in the analysis of the coefficient of determination it can be known that brand transfer decisions are influenced by sales promotion, product quality and consumer dissatisfaction by 30.6%, and the rest is influenced by other factors